Pengaruh Harga, Kualitas Produk, dan Pelayanan terhadap Kepuasan Pelanggan di Toko Domora Freshbakery - Nasution, Nadya Eka Putri Ramadhani; Nasution, Amrin Mulia Utama (Mahesa Research Center, 2024)
This research aims to analyze the influence of price, product quality, and service quality on customer satisfaction at the Domora Fresh Bakery Cake Bakery Cake Shop in Tanjung Morawa sub-district and analyze how to increase customer satisfaction at the Domora Freshbakery Tanjung Morawa Shop. Data was collected through observation and questionnaires from 685 Domora Fresh Bakery Cake customers. A sample of 87 respondents was taken using non-probability sampling techniques. This research uses a qualitative approach and analyzes data with SEM PLS 3.0. The results of this research show that the factors of price, product quality, and service quality significantly influence customer satisfaction at the Domora Freshbakery Store, each with a significance value of 0.003. To increase customer satisfaction, it is necessary to evaluate prices, improve product quality, improve service, and create a pleasant shopping experience. Additionally, regular evaluation through surveys and data analysis will ensure the effectiveness of implemented improvements, supporting customer satisfaction and business success.